Protocirrineris (Polychaeta:Cirratulidae) in South Africa and description of two new species - Elias, Rodolfo (2019)
Introduction: The knowledge of polychaetes in the subtropical region of Africa benefited from the activity of J. Day. However, 50 years after the publication of his Monograph of the Polychaeta of southern Africa, it is necessary to reconsider the identity of the Cirratulidae due to changes in the diagnostic characters and new approaches to the taxonomy of the group to corroborate the status of cosmopolitan species in this region. Objective: We hypothesize that biodiversity of multitentacular Cirratulidae polychaetes has been significantly underestimated in southern Africa. Methods: The present work analyzes material deposited in the Iziko museum, as well as recently collected specimens, using scanning electron microscope to identify them. Results: The material corresponds to two new species belonging to the genus Protocirrineris. Protocirrineris strandloperarum sp. nov. is characterized by having the tentacular filaments between the chaetigers 5 to 10-12 and the first pair of branchiae from chaetiger 7, and P. magalhaesi sp. nov. is characterized by having tentacular filaments between chaetigers 4-8 and the first pair of branchiae from chaetigers 2 or 3. Descriptions of these species, with light and scanning electron microscope images, are given. Schematic drawings of the two new species are shown comparatively with diagnostic characters. Conclusions: The use of new techniques enables discovery of new taxonomic characters and two new species of the genus. The diversity of Cirratulidae polychaetes is underestimated also in the subtropical and tropical regions of Africa.